Mind out of Place: Transhuman Spirituality - Farman, Abou (Journal of the American Academy of Religion, 2019)
Transhumanism, as social movement and ideology, pushes for the technoscientific transcendence of the limits of the human. Some within the movement have also adopted terms like religion and spirituality to denote their own groups and goals and describe their metaphysical forays. Secularism, which is to contain religion and define its domain and boundaries clearly, and maybe eventually replace it, keeps generating religion and spirituality as its own effect. Transhumanism presents a complex technoscientific case of this. The question is not whether transhumanism is religious or is a religion but rather what kind of new formations and subjectivities, new allegiances and attractions, are emerging in the secular interplay of religion, spirituality, science, and technology, especially as put into play by transhumanism—that is, more broadly speaking, as put into play in the transitional human space in which technology, power, and ideology are changing the way we can be humans.